Cradle 2 the grave - Silver, Joel; Bartkowiak, Andrzej ([Burbank, CA] : Warner Bros. Pictures, 2003)
Gangsters aid the police when their leader's daughter is kidnapped and the ransom is a bounty of priceless diamonds. It is also learned that a plot is underway to distribute a deadly new weapon of war
Executive producer, Herbert W. Gains ; editor, Derek G. Brechin ; story, John O'Brien
ast: Jet Li, Anthony Anderson, Kelly Hu, Tom Arnold, Dmx
VCD format
Keywords: Violence in motion pictures